IoT Facing Covid-19: A Classification Modeling - Jorge Gustavo Moreno LÃ³pez (IJAIT (International Journal of Applied Information Technology), 2022)
The sudden and disruptive break out of Covid-19 has a significant impact on various sectors. On the other hand, IoT solutions, with an important time and importance in the literature, offer some applications developed to mitigate the effects of the pandemic which affects worldwide. This article aims to analyze the main trends in IoT Healthcare solutions, specifically those aimed at the context of the pandemic. To this end, a systematic literature review is carried out on the main search engines available. As a result, through the classification of articles by the applicability function of "things", the scope is analyzed from a double perspective, IoT - Covid 19 and IoT - Healthcare. Additionally, the metamodeling of the main findings of the study and their respective instances is presented.